Evaluation of Psychological Wellbeing of Mothers of Children with Intellectual Disabilities in Ongata Rongai, Kajiado County, Kenya - Manyara , Nancy K.; Mwarari , Catherine N. (African Journal of Education,Science and Technology (AJEST), 2020)
It is projected that up to 20% of children and adolescents globally experience some form of intellectual disability rendering them incapable of self-care and independent living. Parenting these children has adverse effect on the psychological and social wellbeing of the mothers due to the demands of care and other parental obligations. The objective of this mixed methods study was to evaluate the emotional health of mothers of children with intellectual disabilities. Questionnaires and interviews were used to collect data from 94 mothers of children with intellectual disabilities living in Ongata Rongai, Kajiado County, Kenya. Results indicated that anxiety, stress, depression, bitterness and low self-esteem were some of the negative emotional experience by mothers parenting children with intellectual disabilities. The study recommends availing of psychosocial support for mothers parenting children with intellectual disabilities to improve their psychological wellbeing.